Mainstreaming gender into water management modelling processes. (May 2020) - Packett, Evangeline; Grigg, Nicola J.; Wu, Joyce; Cuddy, Susan M.; Wallbrink, Peter J.; Jakeman, Anthony J.
Abstract: Although the Dublin principles of Integrated Water Resource Management (IWRM) are well-established, the third principle on gender is commonly missing in practice. We use gender mainstreaming to identify examples where gender-specific perspectives might influence water resource management modelling choices. We show how gender considerations could lead to different choices in all modelling phases, providing examples from three familiar components of modelling practice: (a) problem framing and conceptualisation, (b) model construction, documentation and evaluation and (c) model interpretation and decision support. We suggest a future approach for integrating gender perspectives in modelling. Including gender dimensions could strengthen modelling results by engaging with a range of stakeholders and highlighting questions, knowledge, values and choices that may otherwise be overlooked. Such an approach won't always result in a different model and results. At the very least it's a mechanism to explore and reveal gendered assumptions knowingly, or unknowingly, embedded into the model. Highlights: Gender considerations could lead to different biophysical modelling choices. Gender perspectives can reveal questions, knowledge and values that should not be ignored. Gender mainstreaming approaches can be applied to all stages of modelling practice.